Teneurin and TCAP Phylogeny and Physiology: Molecular Analysis, Immune Activity, and Transcriptomic Analysis of the Stress Response in the Sydney Rock Oyster (Saccostrea glomerata) Hemocytes - Abramov, Tomer; Suwansa-ard, Saowaros; da Silva, Patricia Mirella; Wang, Tianfang; Dove, Michael; O’Connor, Wayne; Parker, Laura; Lovejoy, David A.; Cummins, Scott F.; Elizur, Abigail (Frontiers in Endocrinology, 2022)
Teneurin C-terminal associated peptide (TCAP) is an ancient bioactive peptide that is highly conserved in metazoans. TCAP administration reduces cellular and behavioural stress in vertebrate and urochordate models. There is little information for invertebrates regarding the existence or function of a TCAP. This study used the Sydney rock oyster (SRO) as a molluscan model to characterize an invertebrate TCAP, from molecular gene analysis to its physiological effects associated with hemocyte phagocytosis. We report a single teneurin gene (and 4 teneurin splice variants), which encodes a precursor with TCAP that shares a vertebrate-like motif, and is similar to that of other molluscan classes (gastropod, cephalopod), arthropods and echinoderms. TCAP was identified in all SRO tissues using western blotting at 1-2 different molecular weights (~22 kDa and ~37kDa), supporting precursor cleavage variation. In SRO hemolymph, TCAP was spatially localized to the cytosol of hemocytes, and with particularly high density immunoreactivity in granules. Based on 'pull-down' assays, the SRO TCAP binds to GAPDH, suggesting that TCAP may protect cells from apoptosis under oxidative stress. Compared to sham injection, the intramuscular administration of TCAP (5 pmol) into oysters modulated their immune system by significantly reducing hemocyte phagocytosis under stress conditions (low salinity and high temperature). TCAP administration also significantly reduced hemocyte reactive oxygen species production at ambient conditions and after 48 h stress, compared to sham injection. Transcriptomic hemocyte analysis of stressed oysters administered with TCAP demonstrated significant changes in expression of genes associated with key metabolic, protective and immune functions. In summary, this study established a role for TCAP in oysters through modulation of physiological and molecular functions associated with energy conservation, stress and cellular defence.